Shape memory alloys : modeling and engineering applications - Lagoudas, Dimitris C. (Springer, 2017)
This book provides a working knowledge of the modeling and applications of shape memory alloys (SMAs) to practicing engineers and graduate and advanced undergraduate students with an interest in the behavior and utility of active or multifunctional materials and "smart" structures. SMAs represent a unique material class with the ability to recover seemingly permanent deformations and provide large forces upon heating. These interesting characteristics have led to an ever-expanding variety of engineering applications which address design problems requiring high force actuation in a confined environment. Such applications range from morphing aerospace structures to medical stents and other biomedical devices.